Constitutional Court of the Republic of Indonesia: Does the Ultra Petita Principle Reflect the Truth of Law? - Bagus Hermanto; I Gede Yusa; Nyoman Mas Aryani (Fiat Justisia: Jurnal Ilmu Hukum, 2020)
Constitutional Court is one of the conductors in Indonesia’s judicial power as regulated by Article 24 (2) and Article 24C (1) through (6) of the 1945 Constitution of the Republic of Indonesia, that adjudicates at the first and last levels whose decision is final including in the context of judicial review in the Constitutional Court. The provisions of H.I.R. and R.Bg. firmly reflect one of the principles in the civil procedural law, namely ultra petita, that represent judges prohibition from making decisions beyond what is requested. However, the practice in the Constitutional Court found several Constitutional Court Decisions classified as ultra petita decisions so that there is an academic step to justify the existence of Constitutional Court ruling that determine as ultra petita decisions. This study aims to find the justification of the Constitutional Court in deciding ultra petita through a philosophical, theoretical and legal dogmatic perspective. This study used a normative legal method with the conceptual approach, case studies approach, and legislation or statutory approach. This study shows that based on characteristics of cases under the authority of the Constitutional Court, it cannot be said that the prohibition of ultra petita can be applied to justice in the Constitutional Court, both from a philosophical, theoretical, and legal dogmatic based on several Constitutional Court Decision.